Strategi Pengajaran Inovatif Untuk Anak Usia Dini dalam Memanfaatkan Ragam Metode Pembelajaran di PAUD - Rachman, Syahnas Alya; Salsabila, Nazua; Syahrani, Suci; Febriyanti, Uzi Fauziyah; Hasanah, Lathipah (Early Childhood Islamic Education, 2024)
This research aims to identify innovative teaching strategies that can holistically improve children's learning and development processes and explore the effectiveness of various learning methods in early childhood education. The method used in this research is library research, namely collecting data or scientific writing aimed at research objects or library data collection which is carried out to solve a problem that is basically focused on a critical and in-depth study of relevant library materials. Data were analyzed using descriptive analysis. The main research results include the effectiveness of innovative teaching strategies in utilizing various learning methods in early childhood education, such as increasing interest in learning, children's cognitive, social, and emotional development, and parental involvement in the learning process. Conclusion Innovative teaching strategies that utilize a variety of learning methods have a positive impact on early childhood education. This method can increase children's involvement and understanding effectively.